Highly efficient one-pot multi-component synthesis of alpha-aminophosphonates and bis-alpha-aminophosphonates catalyzed by heterogeneous reusable silica supported dodecatungstophosphoric acid (DTP/SiO2) at ambient temperature and their antitubercular eval - Mulla, Shafeek Abdul Rashid; Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Gample, Suvarna P.; Sarkar, Dhiman (RSC Advances, 2014)
A highly efficient one-pot multi-component reaction (MCR) protocol over DTP/SiO2 has been developed for the synthesis of alpha-aminophosphonate derivatives (4a-x) in excellent yields. The alpha-aminophosphonate derivatives were for the first time evaluated for their antitubercular activity against the M. tuberculosis H37Ra (MTB) strain. An evaluation of the data on the cytotoxicity and antimicrobial activity shows that 4n and 4v are promising antitubercular agents.